Pemberdayaan Masyarakat Pesisir Desa Sanggaran melalui Pelatihan Pengolahan Hasil Laut Berbasis Kearifan Lokal - Alwi, Bashori; Eli Masnawati (Universitas Darunnajah, Jakarta, Indonesia, 2025)
A deliberate attempt to enhance social resilience and economic well-being in coastal regions is empowering coastal communities. Through training in seafood processing based on local wisdom, this programme seeks to improve the community's abilities and independence in Sanggaran Village, Tambak Lekok Subdistrict. Using plentiful marine resources, such fish and shrimp, to create value-added goods like fish floss, shrimp crackers, and fish nuggets is the main focus of the course. The implementation strategy uses a participative approach and includes socialisation, demonstration, production support, and basic marketing training. The findings demonstrate that community members have become more proficient in the economical, creative, and hygienic processing of seafood. Additionally, the rise of small family-run businesses suggests that coastal dwellers are becoming more conscious of entrepreneurship. This practice reinforces local knowledge values in protecting marine resources and promoting social solidarity, in addition to improving the economy. As a result, this programme functions as a long-term paradigm for local potential-based coastal economic empowerment.